The Accuracy of Risanto's Formula and Ultrasound Measurement in Estimating Fetal Weight - Pietersz, Elsina Krisnawati; Rachman, Irwan Taufiqur; Siswosudarmo, Risanto (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Accurate estimated fetal weight (EFW) is crucial in determining delivery management. Several methods to estimate fetal weight were used such as abdominal palpation, measurement of symphisis fundal height (SFH), and ultrasound examination. Risanto’s formula based on Indonesian population had been already proven to be more accurate than Johnson’s formula. The formula was as follows: Y = 125 X - 880 where Y was EFW in grams, X was SFH in cm, and 125 was the constanta.Objective: To compare the accuracy of Risanto’s formula and ultrasound examination in estimating fetal weight.Method: A cross sectional study was carried out in Sardjito hospital, Faculty of Medicine Universitas Gadjah Mada, from March 2013 to March 2014. A total of 400 pregnant women meeting the inclusion criteria at 37 – 42 weeks of gestation were recruited. The estimated fetal weight using Risanto’s formula (R_EFW) was compared to the estimated fetal weight using ultrasound measurement (U_EFW). The U_EFW was done by obstetricians on duty or senior residents using Hadlock’s formula. Actual birth weight (ABW) was measured using the same calibrated baby scale. Accuracy was determined by comparing the mean difference between the R_EFW minus ABW (ΔR_EFW) and the U_EFW minus ABW (ΔU_EFW). Paired t-test was used for statistical analysis.Result and Discussion: The mean ABW was 3025.3 ± 414.6 gram and the mean R_EFW was 2972.7 ± 365.4 grams, while the mean U_EFW was 3058.7 ± 423.2 grams. The mean ΔR_EFW was lower than the mean ΔU_EFW (178.2 ± 147.6 grams vs 197.5 ± 155.4 grams; 95% CI 1.24 – 36.68; p = 0.04).Conclusion: Risanto’s formula was more accurate than ultrasound measurement in estimating fetal weight.Keywords: Estimated fetal weight, Risanto’s formula, Ultrasonography, Fundal height